Integrity Preserved Multifactor Authentication Based Automated Ticketing System - S. Sri Hari , K. Vishal Vinod , P. Hemanth Kumar , Harini G ,N. Harini (International Journal of Advanced Science and Technology, 2020)
The growth of the new technologies and inculcated in services has enabled extension of manualservice counters to technology-driven service counter without human intervention. Today, self-servicetechnologies have attracted customers. This facilitates a user to avail services independent of employeeinvolvement. Examples of self-service technology include ATM, vending machine e.t.c.An automatedservice that supports innovative ticketing is proposed in this paper. The proposed concept supportscloud-based storage of passenger, schedule and ticket details. To ensure data integrity the paymenttransactions are stored in the blockchain. The UI design has been built as a web app and tested with aselective group of users. The removal of the data entry part at the time of requesting/deleting a ticket isreplaced with a QR scanning module to avoid wastage of time and human errors during user input. Thesystem uses a tokenless factor (Mobile phones) to complete the ticket requisition and payment.